The Principle of Protecting the Best Interests of the Child in Shia Jurisprudence and Iran's Legal System with Emphasis on Custody (New Understanding of a Traditional Legal Concept). (January 2019) - Noori, Seyed Masoud; Torabi, Maryamossadat
In this article, children's rights will be studied in the Iranian legal system with remarks on its references in the Shia Jurisprudence. One of the main issues regarding children, is their guardianship, custody or tutorship. The Iranian legal system, same as the Shia Jurisprudence, has always kept the best Interest of the child as an essential ground for law making. Referring to court decisions; it is evident that control of the guardianship on the child is limited by the best interests of the child, because this interests is what we are sure to understand from the reason of custody of the child and that this system is designed only to secure child's best interests since he/she might be incapable to secure his/her interests alone. The Iranian legal system, especially in the family law section is based on the Islamic rules. The main documents in the Shia Jurisprudence in Islam are Quran, Hadith, Consensus and reasoning which will be defined herein. In addition, a more recent review will be made in this study regarding the ratified laws regarding children's rights and international treaties and conventions while focusing on the Convention on the Rights of the Child even though, Iran joined this convention by having several reservations.